Enhanced Lithium-Ion Transport in Polyphosphazene based Gel Polymer Electrolytes. (10th February 2015) - Jankowsky, S.; Hiller, Martin M.; Fromm, O.; Winter, M.; Wiemhöfer, H.-D.
Highlights: "MEEP" based gel polymer electrolytes: high ionic conductivities ( σ total = 2.3 mS cm −1 at 30 °C and high lithium transference number ( T + = 0.31 at 90 °C) . Electrochemically stable vs. lithium metal to 4.5 V. 500 cycles of lithium plating/stripping without dendrite formation. High capacity of 140 mAh g −1 using "MEEP" gel polymer electrolyte with LiFePO4 cathode at 5 C discharge rate. Abstract: A detailed electrochemical study is presented of the lithium ion transport in polyphosphazene based gel polymer electrolytes. The polyphosphazene poly[bis(2-(2-methoxyethoxy) ethoxy) phosphazene (MEEP) was chosen for the polymeric network. In combination with liquid electrolytes (organic carbonates with lithium bis(oxalato) borate and lithium(hexafluoro) phosphate) gel polymer electrolyte membranes with very good ionic conductivities of 2.3 mS cm −1 at 30 °C and high lithium transference numbers of 0.31 at 90 °C were prepared. The investigated electrolytes exhibited very good interface stability at lithium metal electrodes during long term lithium plating/stripping experiments with up to 500 cycles. Discharge rate investigations on full cells consisting of lithium metal ∣ MEEP gel polymer ∣ LiFePO4 delivered high capacities of 140 mAh g −1 at a discharge rate of 5C.